Modeling and study the photovoltaic system, with the influence of internal and external operating conditions - Aicha Djalab; Mohamed Mounir Rezaoui; Noureddine BESSOUS; Imad MERZOUK (Universty of El-oued جامعة الوادي, 2019)
Photovoltaic systems operates to generate electricity. In Algeria is used as a source of alternative electric power connected to the electricity grid. Because of its many benefits, this photovoltaic energy source can be a good replacement or addition to conventional sources of supply of electricity. In this paper, a model of a photovoltaic generator is proposed, where generator uses directly the voltage and current of the photovoltaic panel to search for the operating point corresponding to the maximum power of system photovoltaic studied to proposed control strategy adopted for this system. The objective of this work is to model the photovoltaic system in a way intelligible and understandable to see the influence of the metrological conditions such as illuminance and temperature and the operating parameters internal to photovoltaic system. This allows the development of an on board system in order to control the point of maximum power despite the variation of the temperature, irradiation and the electrical characteristics of the load.
Intervention
Keywords: Photovoltaic system; electricity generation; electricity grid; maximum power; MPPT control